Remote work and eating habits in participants of the Longitudinal Study of Adult Health (ELSA-Brasi) during COVID-19 - Xavier Martins, Haysla (2024)
Introduction: In a scenario of social restrictions to contain the spread of the SARS CoV-2 virus there were changes in the lifestyle and eating habits of populations around the world. Objective: To evaluate eating habits associated with remote work on COVID-19 pandemic. Methods: Cross-sectional study with active workers at ELSA-Brasil during the wave-COVID-19 (July/2020 and February/2021). Data were collected online through self-completed questionnaires. Eating habits represented the dependent variables (“increase in the acquisition of ultra processed foods”, “increase in the acquisition of fresh foods”, “food quality score”, “weekly use of fast-food delivery” and “change in the preparation of meals"). The exposure variable was the work modality (remote or face-to-face). For statistical analysis SPSS 21.0 was used, with significance of p < 0.05. Results: 2463 individuals were evaluated (44 to 83 years old), which, 78 % were working remotely. After adjustment, changes in meal preparation remained associated with remote work, indicating greater chances of cooking more, both for men (OR = 2.45 95 % CI 1.75-3.42) and for women (OR = 2.93 95 % CI 2.19-3.92). No difference was observed between the quality of food score and type of work. However, when evaluating the score using fast-food delivery, those who used it weekly had worse food quality. Conclusion: Individuals in remote work had changes in food preparation, being more likely to cook during the COVID-19. The other eating habits evaluated did not remain associated with the work modality.